How are sexual health clinics in England managing men who have sex with men who refuse to be tested for HIV?. (November 2017) - Hoyos Miller, Juan; Clarke, Emily; Patel, Raj; Kell, Philip; Desai, Monica; Nardone, Anthony
The aim of this study was to ascertain the existence of written policies and common clinical practices in sexual health clinics in England for the management of men who have sex with men who refuse to test for HIV. All sexual health clinics in England ( n  = 223) were invited to complete an online questionnaire in August–September 2014. The questionnaire covered the four domains of clinic policies, management practices, training and monitoring. We assess differences by region. Overall, 92 clinics participated. Only three clinics reported having a written policy. In contrast, most reported having a common agreed practice (94% in London vs. 71.6% elsewhere). When encountering a refusal, 72.2% of the London clinics and 53.4% of the clinics from elsewhere offered a less invasive option. Few clinics (17.4%) provided information on home sampling kits and 74.4% informed about other testing options. Eighty-seven per cent of the clinics recorded the occurrence of refusals, but only 37.8% reviewed the collected data. Providing staff with training was more common in London (94.1% vs. 73.8%). Clear policies should be developed to guide professionals when encountering men who have sex with men who refuse an HIV test. Offering less invasive testing options and information on alternative testing options could be easily introduced into routine practice. Efforts should be made to review monitoring data in order to identify implications of test refusals and introduce improvements in management of refusals.